Mind hunters - Gantz, Robert; Smith, Paul Martin; Kantelinen Tuomas; Harlin, Renny; Brokaw, Cary.; Silver, Jeffrey; Newmyer, Robert; Spikings, Rebecca; Kramer, Wayne, 1965-; Brodbin, Kevin, 1964-; LL Cool J, 1968-; Miller, Jonny Lee.; et al. ([United States] : Dimension Home Video ; Burbank, Calif. : Buena Vista Home Entertainment, Inc., 2005)
Trainees in the FBI's psychological profiling program must put their training into practice when they discover a killer in their midst.
Special features: feature commentary with director -- profiling mindhunters -- stunt sequence -- a director's walk through crimetown.
DVD release of the 2004 motion picture.
Special features: feature commentary with director Renny Harlin ; profiling mindhunters ; stunt sequence ; a director's walk through crimetown.
Director of photography, Robert Gantz ; editor, Paul Martin Smith ; music, Tuomas Kantelinen.
LL Cool J, Jonny Lee Miller, Kathryn Morris, Patricia Velasquez, Clifton Collins Jr, Eion Bailey, Will Kemp, Val Kilmer, Christian Slater.
MPAA rating: R; for violence/strong graphic images, language and sexual content.
DVD ; Dolby digital 5.1 surround sound ; widescreen version ; NTSC, region 1.
Keywords: United States. -- Federal Bureau of Investigation -- Drama; Serial murderers -- Drama; Video recordings for the hearing impaired; Feature films; Drama; DVD-Video discs